PENGUATAN HAK-HAK PENYANDANG DISABILITAS DI BIDANG PENDIDIKAN DI KOTA YOGYAKARTA BERDASARKAN UUD1945 DAN CONVENTION ON THE RIGHTS OF PERSONS WITH DISABILITIES (CRPD) - Nita Ariyani (Universitas Janabadra, 2017)
The rights of Persons with Disabilities obtain legal guarantees both in the Convention on the Rights of Persons with Disabilities (CRPD) and Constitution of the Republic of Indonesia 1945. With the ratification of CRPD by Indonesia through the Law of the Republic of Indonesia Number 19 Year 2011 on The Ratification of the Convention on the Rights of Persons with Disabilities, then all legal products relating to the rights of persons with disabilities, especially in this research, emphasize in the education sector in Yogyakarta city must be based on the provisions in the Constitution of the Republic of Indonesia 1945 and the CRPD. The purpose of this research is to know, understand, review and analyze the strengthening of the rights of people with disabilities in the education sector in Yogyakarta City based on the Constitution of the Republic of Indonesia 1945 and CRPD. This research also aims to know, understand , reviewing and analyzing the juridical constraints faced in the context of strengthening the rights of people with disabilities in the city of Yogyakarta.The type of research used is normative juridical research that is focused to study the application of rules or norms in positive law. The approach method used in this research is statute approach, Analytical Approach, and Case approach. As a follow-up to the ratification of CRPD and also the mandate of the Constitution of the Republic of Indonesia 1945 in particular with regard to the rights of persons with disabilities in the field of education, it is necessary to implement an implementing regulation at the local level of Yogyakarta City to carry out the mandate of the Constitution of the Republic of Indonesia 1945 and the CRPD. The strengthening of the rights of disability in the field of education is experiencing some juridical constraints that must be addressed immediately.Keywords: Reinforcement, Disability Rights, Education, Constitutionof the Republic of Indonesia 1945, CRPD